(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
In the paper the stylistic functions which parenthetic constructions perform in the texts of scientific and publicistik styles of Ukrainian language are compared. Common and specific features of the parenthetic constructions functioning for each style are uncovered.